A Profession has Essential Influence on a Person’s Character - Ketevan Kakhiani (Genius Journals, 2021)
A profession has essential influence on a person’s character. Choosing profession is connected with personal characteristics. When people of certain profession have common features, there specifics can be conditioned not only by a secondary influence of a professional role but the fact that a certain profession is chosen by people with originally similar inclinations. Stereotypes are harmful for professional activity as do not promote to refreshing knowledge and mastering professional skills. Knowing the stereotypes of memory, perception and mind formed with representatives of certain professions, gives them opportunity to avoid professional deformation having negative impact on work and society.
Keywords: Profession; professional stereotypes; professional deformation; professional position